Household heating in the light of climate change - Paládi, Mónika; Tóth, József (Acta Geographica Debrecina Landscape & Environment series, 2014)
Greenhouse gas emissions resulting from anthropogenic activities play a significant role in climate change. The residential heating should be mentioned one of the main polluting source of greenhouse gases.This paper aims to give a comprehensive view about the amount of CO2 emission as well as objectives and strategies for reduction the GHG emission. In addition, we illustrate the example of an average Hungarian family house (100 m2 ), that biomass-based energy production what extent can reduce the current very high degree carbon dioxide emissions. We prepared investment analysis, as to what kind of ecological and economic benefits may result in heating modernization projects of a four-member family home. Additionally, a calculation method of CO2 emission from heating is demonstrated on the basis of IPPC report (2006); the role of biomass is explained in heating; furthermore I give an overview analysis about the significance of forests for reduction of CO2 concentration.